Polycyclic Aromatic Hydrocarbon Content of Breast and Leg’s Meat of Indonesian Native Duck - Sinaga , Kurniawan; Legowo, Anang M.; Bintoro, V. Priyo; Suprijatna, Edjeng; Pramono, Yoyok B. (International Journal of Poultry Science, 2014)
Duck’s leg and breast of Indonesian native duck were analized in laboratory to determine polycyclic aromatic hydrocarbon (PAH) such as naphthalene, acenaphtene, phenentrene, flourantene, pyrene, benzoantrasene and perylene. The result showed that naphthalene, flourantene, pyrene, benzoantrasene and perylene in leg’s duck was higher than breast duck. Total fat of legs (5.87%) were higher than breast (3.31%). This result showed that total fat of raw duck meat influence PAH formation. Antioxidant activity of leg was higher than breast’s duck (8.79% : 5.1%). This result showed that endogenous antioxidant did not able to prevent PAH formation.